The prognostic value of neurofilament levels in patients with sepsis-associated encephalopathy - A prospective, pilot observational study. - Johannes Ehler; Axel Petzold; Matthias Wittstock; Stephan Kolbaske; Martin Gloger; Jörg Henschel; Amanda Heslegrave; Henrik Zetterberg; Michael P Lunn; Paulus S Rommer; Annette Grossmann; Tarek Sharshar; et al. (PLoS ONE)
Sepsis-associated encephalopathy (SAE) contributes to mortality and neurocognitive impairment of sepsis patients. Neurofilament (Nf) light (NfL) and heavy (NfH) chain levels as biomarkers for neuroaxonal injury were not evaluated in cerebrospinal fluid (CSF) and plasma of patients with sepsis-associated encephalopathy (SAE) before. We conducted a prospective, pilot observational study including 20 patients with septic shock and five patients without sepsis serving as controls. The assessment of SAE comprised a neuropsychiatric examination, electroencephalography (EEG), magnetic resonance imaging (MRI) and delirium screening methods including the confusion assessment method for the ICU (CAM-ICU) and the intensive care delirium screening checklist (ICDSC). CSF Nf measurements in sepsis patients and longitudinal plasma Nf measurements in all participants were performed on days 1, 3 and 7 after study inclusion. Plasma NfL levels increased in sepsis patients over time (p = 0.0063) and remained stable in patients without sepsis. Plasma NfL values were significantly higher in patients with SAE (p = 0.011), significantly correlated with the severity of SAE represented by ICDSC values (R = 0.534, p = 0.022) and correlated with a poorer functional outcome after 100 days (R = -0.535, p = 0.0003). High levels of CSF Nf were measured in SAE patients. CSF NfL levels were higher in non-survivors (p = 0.012) compared with survivors and correlated with days until death (R = -0.932, p<0.0001) and functional outcome after 100 days (R = -0.749, p<0.0001). The present study showed for the first time that Nf levels provide complementary prognostic information in SAE patients indicating a higher chance of death and poorer functional/cognitive outcome in survivors.